2016
DOI: 10.1152/ajprenal.00512.2015
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of low-dose cisplatin in mice induces fibrosis

Abstract: Cisplatin, a chemotherapeutic used for the treatment of solid cancers, has nephrotoxic side effects leading to acute kidney injury (AKI). Cisplatin cannot be given to patients that have comorbidities that predispose them to an increased risk for AKI. Even without these comorbidities, 30% of patients administered cisplatin will develop kidney injury, requiring the oncologist to withhold or reduce the next dose, leading to a less effective therapeutic regimen. Although recovery can occur after one episode of cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
118
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 51 publications
5
118
0
1
Order By: Relevance
“…Consistent with previous publication, 18 our data indicated that CP initially triggers acute tubular injury; however, multiple times of CP injection lead to impaired renal function with tubulointerstitial fibrosis. Consistent with previous publication, 18 our data indicated that CP initially triggers acute tubular injury; however, multiple times of CP injection lead to impaired renal function with tubulointerstitial fibrosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous publication, 18 our data indicated that CP initially triggers acute tubular injury; however, multiple times of CP injection lead to impaired renal function with tubulointerstitial fibrosis. Consistent with previous publication, 18 our data indicated that CP initially triggers acute tubular injury; however, multiple times of CP injection lead to impaired renal function with tubulointerstitial fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the clinic significance of CP's acute and/or chronic nephrotoxicity; here, we established an AKI-CKD murine model by weekly CP intraperitoneal injection for 2-4 times. Consistent with previous publication, 18 our data indicated that CP initially triggers acute tubular injury; however, multiple times of CP injection lead to impaired renal function with tubulointerstitial fibrosis. These data indicated that the AKI-CKD murine model is successfully set up in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent evidence has shown severe AKI causes abnormal cellular repair and fibrosis, leading to chronic diseases and end stage renal disease (ESRD). AKI is characterized by sudden decline in renal function over a short time period, and it is always induced by hemodynamic, hypoxic, mechanical, and toxic insults [1,2]. Although programmed cell death and inflammation are believed to play roles in the pathophysiological process of AKI, a detailed mechanism and effective therapy are yet to be determined [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Renal fibrosis is the final common result in loss of kidney function. TGFβ-Smad signaling has been determined to contribute in nephrotoxicity [60][61][62]. TGFβ signaling pathway plays multiple functions in cytokine-mediated signaling in many cell types, conditioning them for differentiation, survival, apoptosis and fibrosis [63].…”
Section: Discussionmentioning
confidence: 99%